The Socioeconomic Profile of Well-Funded Public Libraries: A Regression Analysis - Carlozzi, Michael (Evidence Based Library and Information Practice, 2018)
Abstract Objective – This study aimed to explore the well-established link between public library funding and activity, specifically to what extent socioeconomic factors could explain the correlation. Methods – State-level data from the Massachusetts Board of Library Commissioners were analyzed for 280 public libraries using two linear regression models. These public libraries were matched with socioeconomic data for their communities. Results – Confirming prior research, a library’s municipal funding correlated strongly with its direct circulation. In terms of library outputs, the municipal funding appeared to represent a library’s staffing and number of annual visitations. For socioeconomic factors, the strongest predictor of a library’s municipal appropriation was its “number of educated residents.” Other socioeconomic factors were far less important. Conclusion – Although education correlated strongly with library activity, variation within the data suggests that public libraries are idiosyncratic and that their funding is not dictated exclusively by the community’s socioeconomic profile. Library administrators and advocates can examine what libraries of similar socioeconomic profiles do to receive additional municipal funding.